2010
DOI: 10.1007/s00192-010-1116-2
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index does not influence the outcome of anti-incontinence surgery among women whereas menopausal status and ageing do: a randomised trial

Abstract: We found that BMI does not influence the clinical effectiveness of SUI treatment, whereas both menopause and ageing had a detrimental influence on the final outcome of the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 21 publications
3
38
1
Order By: Relevance
“…So far, however, only one study has been reported for the relationship of obesity and TOT outcomes. Rechberger et al conducted 269 retropubic and 268 transobturator sling procedures and demonstrated that BMI does not influence the clinical effectiveness of SUI treatment [15]. However, they did not assess voiding symptoms, and we believe that the retropubic approach may have a greater chance of de novo urgency.…”
Section: Discussionmentioning
confidence: 91%
“…So far, however, only one study has been reported for the relationship of obesity and TOT outcomes. Rechberger et al conducted 269 retropubic and 268 transobturator sling procedures and demonstrated that BMI does not influence the clinical effectiveness of SUI treatment [15]. However, they did not assess voiding symptoms, and we believe that the retropubic approach may have a greater chance of de novo urgency.…”
Section: Discussionmentioning
confidence: 91%
“…20 Among different techniques which can be used in SUI treatment, MUS is effective in obese patients. 11,12 There are several studies about incontinence surgery in obese patients, but the results of these studies are contradictory. Most of the studies investigating the results of sling procedures comprise the surgical outcomes of TVT procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, midurethral sling (MUS) procedures have been effective with minimal complications in obese patients. [10][11][12] However the influence of obesity on surgical outcomes of TOT procedure is still controversial and the situation is more complicated when it comes to severely obese patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the research, retropubic and transobturator sling procedures were applied to 537 female patients with SUI. After an 18 month follow-up, 398 patients were evaluated, and it was demonstrated that BMI did not have any affect on the surgery result, while menopausal status and age were found to be independent risk factors decreasing the success of the sling procedures [21]. In a study with 184 female patients where collagen was used as the periurethral injection material [22], similar to our study, it is reported that the previous anti-incontinence treatment is an important factor contributing to the success of the treatment in the patients who had been reported 'cure' for more than one year after the injection.…”
Section: Discussionmentioning
confidence: 99%